Molecular identification of fungal communities in a soil cultivated with vegetables and soil suppressiveness to Rhizoctonia solani - Val-Moraes, Silvana Pompéia [UNESP]; Nascimbem Pedrinho, Eliamar Aparecida [UNESP]; Lemos, Eliana Gertrudes Macedo [UNESP]; Carareto-Alves, Lucia Maria [UNESP] (Hindawi, 2013)
Fungi constitute an important part of the soil ecosystem, playing key roles in decomposition, cycling processes, and biotic interactions. Molecular methods have been used to assess fungal communities giving a more realistic view of their diversity. For this purpose, total DNA was extracted from bulk soils cultivated with tomato (STC), vegetables (SHC), and native forest (SMS) from three sites of the Taquara Branca river basin in Sumaré County, São Paulo State, Brazil. This metagenomic DNA was used as a template to amplify fungal 18S rDNA sequences, and libraries were constructed in Escherichia coli by cloning PCR products. The plasmid inserts were sequenced and compared to known rDNA sequences in the GenBank database. Of the sequenced clones, 22 were obtained from the SMS sample, 18 from the SHC sample, and 6 from the STC sample. Although most of the clone sequences did not match the sequences present in the database, individual amplified sequences matched with Glomeromycota (SMS), Fungi incertae sedis (SMS), and Neocallimastigomycota (SHC). Most of the sequences from the amplified taxa represent uncultured fungi. The molecular analysis of variance (AMOVA) indicated that fluctuations observed of haplotypes in the composition may be related to herbicide application. © 2013 Silvana Pompéia Val-Moraes et al.